ENGARUH LAYANAN BIMBINGAN KELOMPOK TEKNIK DISKUSI TERHADAP KEMAMPUAN KOMUNIKASI ANTAR PRIBADI SISWA KELAS XI DI SMK PELITA ALAM BEKASI - Fadhil Hardiansyah; Dita Rizki Prasitia (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2016)
The influence of technical discussion group tutoringservice of interpersonal communication skills of students of Class XI in SMK Lamp NatureBekasi. Thesis: the educational guidance counseling Degree programs the University of IslamAS'SYAFI ' IYAH JOIN, 2015.This research aims to know the influence or whether tutoring service engineeringgroup discussion of interpersonal communication skills of students. The hypothesis putforward in the study is